PENGARUH INFLASI DAN NILAI TUKAR TERHADAP PERGERAKAN INDEKS HARGA SAHAM GABUNGAN DI BURSA EFEK INDONESIA (PERIODE JANUARI 2010-DESEMBER 2015) - Rumbiati Rumbiati (Universitas Indo Global Mandiri)
Macro economy policy thats goverment using to counter of destruction of global economic crisisst to influence portofolio invesment activity doing buy market broker especially on capital investment in capital market.This paper analyzes the relationship between variable inflation, and exchange rate and Indonesian stock market by applied. This paper focused on January 2010 until December 2015. The result of simultaneous the inflation and exchange rate effect on stock market in Jakarta Stock Exchage. While patially the inflation is negative effect to stock market. And exchange rate is positive effect to stock market in Jakarta Stock Market.Key world : Inflation, exchange rate, and stock market